Investigations of dispersion characteristics of microwave/optical guided wave structures by using transmission line matrix method. - Qiu, Bing. (University of Ottawa (Canada), 1993)
This thesis presents a new three-dimensional space (3D) condensed node TLM space (Transmission Line Matrix) algorithm for the analysis of dispersion characteristics of microwave/optical guided wave structures. This new algorithm requires much less computer memory and computation time than the conventional 3D condensed node TLM. The application of this new algorithm to the modelling of inhomogeneous, lossy, and unbounded guided structures is investigated. More specifically, techniques such as variable mesh size, absorbing boundaries conditions, are introduced in the algorithm. The error sources, effects due to excitation and output point location are analysed and suggestions for more efficient and accurate modelling of complicated geometries are performed. In particular, special treatment is implemented to accurately model curved boundaries. Finally, the dispersion characteristics of various kinds of rectangular and circular guided structures, are calculated by using this new algorithm. It is found that the results obtained agree fairly well with those observed by theoretical or other proved numerical methods.
Keywords: Engineering, Electronics and Electrical.